Peran Sosialisasi Hukum dalam Pencegahan Perilaku Bullying : Kajian Hukum Pidana dan Perlindungan Anak di Desa Sumeith Pasinaro - Cut Charolina Pattiwaellapia; Ronald Darlly Hukubun; Riskia Tirta Nirwana Sopacua; Jehuda Daniel Nussy; Rocky Genestho Kubela; Deirdre Livia Petta; Vanessa Yosiana Matital; Abdul Mahid Ukratalo (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Bullying in Indonesian educational settings remains a serious problem that requires widespread attention. Poor legal understanding among children and adolescents, coupled with suboptimal child protection regulations, increases the risk of violence in schools. To address this issue, a "Fight Bullying" outreach program was conducted in Sumeith Pasinaro Village, aimed at improving students' understanding of the definition, forms, impacts, and legal consequences of bullying. This program utilized a qualitative descriptive approach and a participatory education model, involving 47 students from Sumeith Pasinaro Elementary School and Elpaputih 2 Junior High School. The methods employed included material delivery, interactive discussions, and assessments to provide students with an in-depth understanding of the legal education provided. The evaluation results showed a significant increase in students' understanding of bullying, with an average level of understanding reaching 80.83%. Students were able not only to identify the types of bullying but also to understand the long-term impacts on both victims and perpetrators. This outreach program also helped students understand the legal regulations governing bullying and encouraged them to report or stop such acts. This program emphasizes the importance of a planned and sustainable approach involving teachers and parents to prevent bullying, as well as creating a safe learning environment and supporting child protection.